2012
DOI: 10.1007/s10152-012-0312-5
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of decapod larvae in the surface layer of an isolated equatorial oceanic archipelago: the cases of benthic Grapsus grapsus (Brachyura: Grapsidae) and pelagic Sergestes edwardsi (Dendrobranchiata: Sergestidae)

Abstract: Two different decapod larval assemblages inhabit the marine environment of Saint Paul's Rocks, differentiating the inlet from the surrounding oceanic waters. Larvae of the crab Grapsus grapsus and of the holopelagic shrimp Sergestes edwardsi are abundant in superficial waters of the archipelago and have previously been shown to be good indicators of the inlet and adjacent oceanic waters, respectively. We investigated the horizontal, diel and temporal distribution of these species at Saint Paul's Rocks. Horizon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Thus, larvae could be lost in the middle of the ocean or they could eventually reach unusual destinations. Only the first larval stage of Grapsus grapsus is known, but the complete larval development of other grapsid species has been described and the duration of their zoeal phase varies from 30 to 60 days (Brandão et al 2013). Assuming 45 days for the larval plankton phase and using the distance of 2000 km between TR and the equatorial islands, the larvae would need to be transported with an average speed of 0.51 mÁs À1 to survive until settlement and therefore maintain gene flow.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, larvae could be lost in the middle of the ocean or they could eventually reach unusual destinations. Only the first larval stage of Grapsus grapsus is known, but the complete larval development of other grapsid species has been described and the duration of their zoeal phase varies from 30 to 60 days (Brandão et al 2013). Assuming 45 days for the larval plankton phase and using the distance of 2000 km between TR and the equatorial islands, the larvae would need to be transported with an average speed of 0.51 mÁs À1 to survive until settlement and therefore maintain gene flow.…”
Section: Discussionmentioning
confidence: 99%
“…(Freire et al 2011), suggesting that this population experiences harsh environmental conditions. Furthermore, a recent study suggested the occurrence of retention mechanism limiting Grapsus grapsus larvae dispersal (Brandão et al 2013). According to our results, G. grapsus might reach islands up to 700 km apart (SPSPA, FN and RA) but has a low potential of arriving at more distant islands, due to poor larval survival and occurrence of eddies, vortices and discontinuities of the surface currents.…”
Section: Discussionmentioning
confidence: 99%
“…Large neritic larval abundances at coastal stations around oceanic islands are common and may suggest a larval retention (Brandão et al, 2012(Brandão et al, , 2013Landeira et al, 2013) which ensures the maintenance of larvae near their areas of origin (Mcconaugha, 1992;Landeira et al, 2009). …”
Section: Relevance Of Geographical Features and Possible Retention Phmentioning
confidence: 99%
“…This effect increases considerably the planktonic biomass in these environments (Doty and Oguri, 1956;Gove et al, 2016). Additional factors are current, eddies and winds, which may lead to retention, depending on their interaction with the local geological features (Brandão et al, 2012(Brandão et al, , 2013Landeira et al, 2013). Previous studies have observed that in more sheltered (leeward) locations of oceanic islands there was a higher abundance of planktonic organisms than at more external (windward) sites of the islands (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation